2022
DOI: 10.1088/2515-7655/ac86a1
|View full text |Cite
|
Sign up to set email alerts
|

Current status of n-type SnS: paving the way for SnS homojunction solar cells

Abstract: Orthorhombic SnS is a promising thin-film solar-cell material composed of safe and abundant elements with suitable optical properties for photovoltaic application. For approximately two decades, SnS solar cells have employed heterojunction structures with p-type SnS and other n-type semiconductors because undoped SnS typically exhibits p-type electrical conduction. However, their conversion efficiency has remained stagnant at 4–5% for a long time. A breakthrough is required to significantly improve their conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 84 publications
(107 reference statements)
2
15
0
Order By: Relevance
“…Tin sulfide material is a promising semiconductor; it has two stable SnS and SnS 2 phases. Both phases are promising alternatives for absorber layer use in thin film SnS homojunction and heterojunction solar cells (Suzuki et al, 2022), holographic recording system in gas sensors and recently as a novel material for electrodes in lithium ions batteries (Cho et al, 2019; Jiang et al, 1998; Momma et al, 2001). SnS semiconductor is characterized by a high absorption coefficient (α ∼ 10 5 cm −1 ) (Koteeswara Reddy & Ramakrishna Reddy, 2007; Nisha, Kumar, et al, 2022), a direct band gap lying between 1.3 and 1.5 eV (Sun et al, 2012) and is composed with abundant non‐toxic and cheap elements (Engelken et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Tin sulfide material is a promising semiconductor; it has two stable SnS and SnS 2 phases. Both phases are promising alternatives for absorber layer use in thin film SnS homojunction and heterojunction solar cells (Suzuki et al, 2022), holographic recording system in gas sensors and recently as a novel material for electrodes in lithium ions batteries (Cho et al, 2019; Jiang et al, 1998; Momma et al, 2001). SnS semiconductor is characterized by a high absorption coefficient (α ∼ 10 5 cm −1 ) (Koteeswara Reddy & Ramakrishna Reddy, 2007; Nisha, Kumar, et al, 2022), a direct band gap lying between 1.3 and 1.5 eV (Sun et al, 2012) and is composed with abundant non‐toxic and cheap elements (Engelken et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…[4] Thus, despite recent advances made in computational science, experimental approaches can still provide important information for understanding the electronic structures of materials. In this study, tin sulfide (α-SnS, whose crystal structure is shown in Figure S1 in Supporting Information), which is a promising material for thin-film solar cells [5,6] and thermoelectric materials, [7] was used as a model material for angle-resolved photoelectron spectroscopy (ARPES) analysis. ARPES is the only experimental technique that enables the direct observation of the band dispersion based on measurements of both the energy and momentum of electrons in a material.…”
Section: Introductionmentioning
confidence: 99%
“…for efficient solar cells, several works address the implementation of guest atoms into the SnS structure with the aim to push the carrier into the n-doped regime (see ref. 6 and references therein). In addition, the implementation of magnetic guests atoms is a standard approach to introduce spin degrees of freedom into semiconductors.…”
Section: Introductionmentioning
confidence: 99%